PENGARUH IKATAN FINANSIAL , SOSIAL DAN STRUKTURAL TERHADAP LOYALITAS NASABAH DIMEDIASI VARIABEL CORPORATE IMAGE (Studi Kasus Bank Negara Indonesia (BNI) Cabang UNDIP Semarang - Farida, Naili (Faculty of Social and Political Sciences Diponegoro University)
Abstract : Effect of relationship model integration, financial bonding, social bonding and structural bonding to the customer loyalty at Bank Negara Indonesia (BNI) Branch UNDIP Semarang. The location of this research is the city Semarang, purposive sample using sampling, the number of samples in this study as many as 100 customers of Bank BNI, testing of hypotheses in this research using descriptive analysis and regression analysis with path analysis with 5% significance level. The purpose of this study is to investigatege, financia bondingl, socialbonding and structural bonding customes through its corporate image as a mediating variable on customer loyalty Bank Negara Indonesia (BNI) UNDIP semarang.Keyword: financial bonding, social bonding, structural bonding , corporate image and loyalty.permalink: http://ejournal.undip.ac.id/index.php/forum/article/view/3204